Mangroves Ecosystem Conservation Plan in Ujung Alang Village, Kampung Laut District, Cilacap Regency PERENCANAAN KONSERVASI EKOSISTEM MANGROVE DESA UJUNG ALANG KECAMATAN KAMPUNG LAUT KABUPATEN CILACAP - Ratini .; Bambang Sulistyantara; Tati Budiarti (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Mangrove ecosystem have many function such as ecological and economic function. Degradation of mangrove ecosystem occured in Ujung Alang village, Cilacap. The study was aimed to identify mangove ecosystem, to analyze relationship between sosial economy of villagers and mangrove ecosystem, and to formulate the strategy of mangrove ecosystem management. Some analysis were done in this study such as: vegetation analysis, perception analysis, and SWOT analysis. By the vegetation analysis it was found 16 species of mangroves that was dominated by Acanthus ebracteatus (ground cover), Aegiceras corniculatum and Rhizopora mucronata (seedlings), Sonneratia alba (sapling), and Sonneratia caseolaris and Avicennia alba (tree). Perception analysis showed some factors affecting mangrove degradation such as economy, education, and lack of control from the authorities. The strategy of mangrove management are keep the mangrove ecosystem sustainability, increase community involvement in the management of mangrove ecosystem, and Participatory supervision of the community towards the activities in mangrove ecosystem.Key words: conservation, degradation, mangrove, ecosystems, management strategy.